PENGEMBANGAN INDIKATOR 4C’s YANG SELARAS DENGAN KURIKULUM 2013 PADA MATA PELAJARAN MATEMATIKA SMA/MA KELAS XII SEMESTER I - Anggraini, Devi Dwi; Sunardi, Sunardi; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to describe development process of 4C’s indicators that in accordance the curriculum of 2013 in mathematics subject of first semester XII grade of Senior High School/MA. According to P21 4C’s abilites are critical thinking, communication, collaboration, and creativity.Mathematics subjects of first semester XII grade of Senior High School/MA which consist of 3 subjects namely plane geometry, three dimensional objects geometry, ang mathematical statistics. This research based on modified plomp model. This research only uses four phases namely inital investigation phase, designing phase, realisation/construction phase, and test, evaluation, and revision phase. Validity test was conducted by 5 validators which consists of 2 mathematics education lecturer and 3 mathematics teacher. From the data analysis can be concluded that 4C’s indicator that were developed are valid. Keywords: 4C's Indicators, Curriculum 2013, Plomp's Development Model